2009
DOI: 10.5194/aab-52-23-2009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasonic measured ribeye area and fat thickness to the certain traits measured on slaughtered bulls (Short Communication)

Abstract: The aim of this study was to test accuracy of measurements done by Falco 100 (Pie Medical) ultrasonic equipment. 10 Angus, 10 Hungarian Simmental, 10 Limousin and 10 Charolais fattening bulls were measured at the feedlot just before slaughtering. Fat thickness at the rump (P8) and ribeye area (REA) were realized from each animal. After slaughtering, the data of slaughter and carcass weights were collected and carcasses were judged on the base of EUROP system. The database was examined by SPSS 9.0 for Windows. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…Previously, Pfuhl et al (2007) reported differences in cross sectional area of longissimus muscle between Charolais and Holstein bulls.The longissimus muscle area at the 12th rib was significantly lower for Angus and Holstein compared to other genotypes. Török et al (2009) measured via ultrasonic measurements higher ribeye area for Charolais, Angus and Hungarian Simmental bulls than our values. Our measurements were made after dissection at 24 h post mortem, whilst Török et al (2009) measured carcass ribeye area immediately after slaughter.…”
Section: P<005contrasting
confidence: 69%
See 2 more Smart Citations
“…Previously, Pfuhl et al (2007) reported differences in cross sectional area of longissimus muscle between Charolais and Holstein bulls.The longissimus muscle area at the 12th rib was significantly lower for Angus and Holstein compared to other genotypes. Török et al (2009) measured via ultrasonic measurements higher ribeye area for Charolais, Angus and Hungarian Simmental bulls than our values. Our measurements were made after dissection at 24 h post mortem, whilst Török et al (2009) measured carcass ribeye area immediately after slaughter.…”
Section: P<005contrasting
confidence: 69%
“…Török et al (2009) measured via ultrasonic measurements higher ribeye area for Charolais, Angus and Hungarian Simmental bulls than our values. Our measurements were made after dissection at 24 h post mortem, whilst Török et al (2009) measured carcass ribeye area immediately after slaughter.…”
Section: P<005contrasting
confidence: 69%
See 1 more Smart Citation